Resistance training volume does not influence lean mass preservation during energy restriction in trained males. (5th October 2022) - Roth, Christian; Schwiete, Carsten; Happ, Kevin; Rettenmaier, Lukas; Schoenfeld, Brad J.; Behringer, Michael
Abstract : This study investigated the effects of a relatively high‐ versus moderate‐volume resistance training program on changes in lean mass during caloric restriction. Thirty‐eight resistance‐trained males were randomized to perform either a high‐volume (HVG; 5 sets/exercise) or a moderate‐volume (MVG; 3 sets/exercise) resistance training program. Both groups were supervised during lower body training. Participants consumed 30 kcal/kg for 6 weeks after 1 week of weight maintenance (45 kcal/kg), with protein intake fixed at 2.8 g/kg fat‐free mass. Muscle thickness of the m. rectus femoris, body composition, contractile properties, stiffness, mood, and sleep status were assessed at pre‐, mid‐, and post‐study. No significant group × time interaction was observed for muscle thickness of the m. rectus femoris at 50% (∆ [post‐pre] 0.36 ± 0.93 mm vs. ∆ −0.01 ± 1.59 mm; p  = 0.226) and 75% length (∆ −0.32 ± 1.12 mm vs. ∆ 0.08 ± 1.14 mm; p  = 0.151), contractility, sleep, and mood in the HVG and MVG, respectively. Body mass (HVG: ∆ −1.69 ± 1.12 kg vs. MVG: ∆ −1.76 ± 1.76 kg) and lean mass (∆ −0.51 ± 2.30 kg vs. ∆ −0.92 ± 1.59 kg) decreased significantly in both groups ( p  = 0.022), with no between‐group difference detected ( p  = 0.966). High‐volume resistance training appears to have neither an advantage nor disadvantage over moderate‐volume resistance training in terms of maintaining lean mass or muscle thickness. Given that both groups increased volume load and maintained muscle contractility, sleep quality, and mood, either moderate or higher training volumes conceivably can be employed by resistance‐trained individuals to preserve muscle during periods of moderate caloric restriction.